KARAKTERISTIK IBU HAMIL DENGAN PREEKLAMSIADI RSUP PROF.DR.R.D. KANDOU MANADO PERIODE 1 JANUARI - 31 DESEMBER 2015 - Lombo, Giovanna Eunike; Wagey, Freddy W; Mamengko, Linda (JKK (Jurnal Kedokteran Klinik), 2017)
Abstract: Preeclampsia is the kind of hypertension that occurs in pregnant women in the 20th week of gestational age or after delivery, indicated by the rise of blood pressure to >140/90  mmHg and is accompanied by a large amount of protein in the urine (proteinuria), about 300 mg protein in the urine for 24 hours. Preeclampsia is divided into mild preeclampsia and severe preeclampsia. In Indonesia alone, hypertension in pregnant women on 2010 is around 21,5%, 24,7% in 2011, 26,9% in 2012, and 27,1% in 2013. Based on the data from those years, there is an increase of incidence of hypertension in pregnant women. The goal of this research is to discover characteristic of pregnant women with preeclampsia. This study uses a retrospective descriptive study design. Results: On the year 2015, there were 60 patients who got diagnosed with preeclampsia. The age group of 31-35 years old is the highest in number, PER (10%) and PEB (18,3%). The highest type of work, housewife PER (18,3%) and PEB (40%). The highest number of parity in primigravida, PER (18,3%) and PEB (43,3%). Based on the number of delivery happening in 2015, PER (11,7%) and PEB (20%). Nutritional status of obese (BMI > 30,00), PER (20 %) and PEB (53,3%). Hypertension history on those who didn’t have previous hypertension history, PER (25%) and PER (66,7%).Conclusion: the types of preeclampsia that happens the most is the severe preeclampsia at the mean age of 31-35 years old, occurred in housewifes, according to parity number in primigavida who’s gonna have delivery on 2015, with obese BMI control, the previous hypertension story is not obligated to be found.Keyword: preeclampsia, characteristics Abstrak: Preeklampsia adalah hipertensi yang terjadi pada ibu hamil dengan usia kehamilan 20 minggu atau setelah persalinan di tandai dengan meningkatnya tekanan darah menjadi ≥ 140/90 mmHg dan di sertai dengan kadar proteinuria 300 mg protein dalam urin selama 24 jam. Preeklampsia dibagi menjadi preeklampsia ringan dan preeklampsia berat. Di Indonesia, hipertensi pada ibu hamil tahun 2010 (21,5%), tahun 2011 (24,7%), tahun 2012 (26,9%), 2013 (27,1%). Berdasarkan data dari tahun 2010 - 2013 terjadi peningkatan kejadian hipertensi pada kehamilan.. Tujuan penelitian ini yaitu untuk mengetahui karakteristik dari pasien ibu hamil dengan preeklampsia. Jenis penelitian ini menggunakan desain penelitian deskriptif retrospektif. Hasil: pada tahun 2015, terdapat 60 pasien dengan diagnosis Preeklampsia. Kelompok umur tertinggi 31 – 35 tahun, PER (10%) dan PEB (18,3%). Jenis pekerjaan tertinggi ibu rumah tangga, PER (18,3%) dan PEB (40%). Jumlah paritas tertinggi pada primigravida, PER (18,3%) dan PEB (43,3%). Partus yang terjadi pada tahun 2015 terbanyak, PER (11,7%) dan PEB (20%). Status gizi ketegori obesitas (IMT ≥30,00), PER (20%) dan PEB (53,3%). Riwayat hipertensi pada kategori tidak memiliki riwayat hipertensi sebelumnya, PER (25%) dan PEB (66,7%). Kesimpulan: Jenis Preeklampsia yang paling banyak terjadi adalah PEB pada rata-rata umur 31 – 35 tahun, pekerjaan ibu rumah tangga, jumlah paritas pada primigravida, partus pada tahun 2015, status gizi dengan kategori obesitas, riwayat hipertensi sebelumnya tidak ditemukan.Kata Kunci: preeklampsia, karakteristik